2020
DOI: 10.1101/2020.07.08.192443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent Evolution of Pain-Inducing Defensive Venom Components in Spitting Cobras

Abstract: Convergent evolution provides unparalleled insights into the selective drivers underlying evolutionary change. While snakes use venom primarily for predation, and venom composition often reflects diet specificity, three lineages of spitting cobras have independently evolved the ability to use venom as a defensive projectile. Using gene, protein and functional analyses, we show that the three spitting lineages possess venom characterized by an upregulation of PLA2 toxins, which potentiate the action of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Recently, Kazandjian et al. (2020) showed that spitting behavior in cobras has evolved independently in three spitting lineages as a defensive mechanism. Their results demonstrated that venom of cobras from these lineages was endowed with an upregulation of the activity of phospholipase A2 (PLA2) enzyme, a common toxin in venom of snakes, which triggers the activity of venom cytotoxins resulting in the activation of mammalian sensory neurons, thereby causing increased pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kazandjian et al. (2020) showed that spitting behavior in cobras has evolved independently in three spitting lineages as a defensive mechanism. Their results demonstrated that venom of cobras from these lineages was endowed with an upregulation of the activity of phospholipase A2 (PLA2) enzyme, a common toxin in venom of snakes, which triggers the activity of venom cytotoxins resulting in the activation of mammalian sensory neurons, thereby causing increased pain.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution, demography, biology, ecology, and conservation status of the Caspian cobra remain largely undescribed. Even though some molecular studies have investigated Asian and African cobras (Kazandjian et al., 2020; Lin et al., 2008, 2012, 2014; Ratnarathorn et al., 2019; Santra et al., 2019; Wallach et al., 2009; Wüster et al., 2007), the phylogenetic and phylogeographic status, as well as the evolutionary history and population structure of the Caspian cobra in the Trans‐Caspian region, are still poorly known. The only study conducted on the genetic structure and phylogeny of the Caspian cobra in Iran, using 589 base pairs (bp) of the mitochondrial D‐loop region, revealed low genetic diversity and unstructured populations of the Iranian Caspian cobra (Shoorabi et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Foraging hominins were likely to come in contact much more often with terrestrial, diurnally active neurotoxic elapid snakes such as cobras, which would defend themselves against perceived primate predators using their venom(22). The likely reduced susceptibility to α-neurotoxins from cobras might have driven cobras to develop a different kind of defense against hominins in the form of cytotoxins and spitting(15, 24). An evolved form of partial resistance meant that cobra venom was not an effective method to reduce hominin interactions thus cytotoxins and spitting might have evolved in response as a deterrent.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, there is evidence that venomous elapids have evolved some adaptations in response to primates. Spitting in cobras has evolved on three convergent occasions (twice within Naja and again Hemachatus) is a defensive trait that causes intense ocular pain and inflammation, which might have evolved in response to unique behavioural adaptations by anthropoids, particularly early hominines(15). Predation events by natural predators (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation